Structure and properties of austenitic ODS steel 08Cr18Ni10Ti - Velikodnyi, A.N.; Voyevodin, V.N.; Tiкhonovsky, M.A.; Bryk, V.V.; Kalchenko, A.S.; Starostenko, S.V.; Kolodiy, I.V.; Okovit, V.S.; Bovda, A.М.; Onischenko, L.V.; Storogilov, G.Ye. (Вопросы атомной науки и техники, 2014)
Using mechanical alloying, experimental samples of austenitic stainless steel 08Cr18Ni10Ti dispersion hardening
nano systems Y₂O₃-ZrO₂ different composition. The microstructure of samples at various stages of preparation, depending
on the composition of an oxide of the alloying conditions and thermal-mechanical processing. Defined structural
parameters tape sample (particle size, density and size distribution of the precipitates, etc.). The mechanical properties of
tapes at room temperature and at 700 ºC and it is shown that the characteristics ODS steel is significantly higher compared
with a conventional steel, obtained according to the same modes. This difference is particularly significant in the test
conditions at 700 ºC, where the yield strength of ODS steel is 2.3 times higher than for initial steel 08Cr18Ni10Ti.
ODS steel ductility is somewhat lower than the initial one, but its value remains at a level sufficient for the technological
and operational goals. С использованием механического легирования получены экспериментальные образцы аустенитной
нержавеющей стали 08Х18Н10Т, дисперсно-упрочненной нанооксидами системы Y₂O₃-ZrO₂ различного
состава. Изучена микроструктура образцов на разных стадиях получения в зависимости от состава
легирующего оксида и условий механико-термической обработки, определены их структурные параметры
(размер зерен, плотность и распределение выделений по размерам и др.). Измерены механические свойства
лент и показано, что характеристики ДУО стали существенно выше по сравнению с обычной сталью,
полученной по тем же режимам. Особенно существенное различие в условиях испытаний при 700 ºС, где
увеличение условного предела текучести составляет 2,3 раза. Пластичность ДУО стали несколько ниже, чем
у исходной, однако ее величина остается на уровне, достаточном для технологических и эксплуатационных
целей. З використанням механічного легування отримані експериментальні зразки аустенітної нержавіючої
сталі 08Х18Н10Т, дисперсно-зміцненої нанооксидами системи Y₂O₃-ZrO₂ різного складу. Вивчено
мікроструктуру зразків на різних стадіях отримання залежно від складу легуючого оксиду та умов механіко-термічної обробки. Визначено структурні параметри стрічкових зразків (розмір зерен, щільність і розподіл
виділень за розмірами та ін.). Виміряно механічні властивості стрічок при кімнатній температурі і при
700 ºС і показано, що характеристики ДЗО сталі істотно вищі в порівнянні із звичайною сталлю, отриманою
за тими ж режимами. Особливо істотне це розходження в умовах випробувань при 700 ºС, де зростання
умовної межі текучості становить близько 2,3 рази. Пластичність ДЗО сталі трохи нижча, ніж у вихідної,
однак її величина залишається на рівні, достатньому для технологічних та експлуатаційних цілей.